Polymorphism of DNA nucleotide sequence as a source of enhancement of the discrimination potential of the STR-markers - Zemskova, E Yu; Timoshenko, T V; Leonov, S N; Ivanov, P L (Sudebno-meditsinskaia ekspertiza, 2016)
The objective of the present pilot investigation was to reveal and to study polymorphism of nucleotide sequence in the alleles of STR loci of human autosomal DNA with special reference to the role of this phenomenon as a source of the differences between homonymous allelic variants. The secondary objection was to evaluate the possibility of using the data thus obtained for the enhancement of the informative value of the forensic medical genotyping of STR loci by means of identification of single nucleotide polymorphisms (SNP) for the purpose of extending their allelic spectrum. The methodological basis of the study was constituted by the comprehensive amplified fragment length polymorphism (AFLP) analysis and amplified fragment sequence polymorphisms (AFSP) analysis of DNA with the use of the PLEX-ID^TM analytical mass-spectrometry platform (Abbot Molecular, USA). The study has demonstrated that polymorphism of DNA nucleotide sequence can be regarded as the possible source of enhancement of the discriminating potential of STR markers. It means that the analysis of polymorphism of DNA nucleotide sequence for genotyping AFLP-type markers of chromosomal DNA can considerably increase the effectiveness of their application as individualizing markers for the purpose of molecular genetic expertises.